ILMU on-line library catalogue: Author / title / subject search option - Lee, A. (Perpustakaan Universiti Malaya, 1993)
Since the introduction of the on-line library catalogue or OPAC in 1991, library users are able to access the collections in the University of Malaya Library System via OPAC terminals placed in each library. Several brochures have been produced to glJide users when using OPAC. OPAC allows two search options: i) Author/TitlelSubject Search Option and; it) Keyword Search Option. This article will discuss some of the advanced search features of the Author/TitlelSubject Search Option and guide users to refine their search strategy to obtain the required information. Screen information is also explained. The advanced search features for the Keyword Search Option will be discussed in the forthcoming issue .